The Influence of the Technology Acceptance Model on the Decision to Pay ZIS through Digital Payment in Malang City - Nabila Akhiris Rakhmania; Multifiah Multifiah; Iswan Noor (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
The COVID-19 pandemic has increased society's reliance on technology. Today’s society tends to shift its style and behavior towards digital in every activity and transaction, including the payment of Zakat, Infaq, and Shadaqah (ZIS). This study aims to analyze the influence of the Technology Acceptance Model (TAM) on the decision to pay ZIS through digital payment in Malang City. This research uses a quantitative approach with a purposive sampling technique. Primary data was collected through distributing questionnaires to 150 respondents. The data was analyzed using Structural Equation Modeling (SEM) with SmartPLS software version 3. The results showed that the variables perceived usefulness and perceived ease of use had a significant influence on the decision to pay ZIS. This study implies that the perceived ease of use and perceived usefulness of technology can encourage people to make digital payments for ZIS.